2004
DOI: 10.1080/10640260490267779
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate in the Treatment of Comorbid Night Eating Syndrome and PTSD: A Case Study

Abstract: Comorbid chronic sleepwalking with night eating syndrome and posttraumatic stress disorder were treated with topiramate for eight months in an obese 40-year-old woman. Central nervous system side effects of word-finding and memory difficulties were managed with dosage adjustments to a final dose of 100 mg HS. Treatment led to resolution of posttraumatic stress disorder symptoms, night eating episodes, and sleepwalking episodes, with a weight loss of 70 pounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…The heterogeneous clinical symptoms parallel broad biological dysfunction in the hypothalamic-pituitary axis (HPA) (2)(3)(4)(5)(6)(7)(8)(9)(10) and autonomic (ANS) (4,(11)(12)(13) and central nervous system (CNS) functions (14)(15)(16)(17). Previous studies have provided evidence for a low level pro-inflammatory state in PTSD (18)(19)(20)(21)(22). The CNS areas involved are central regulators of the HPA axis and the ANS, and this coordinated dysfunction in PTSD is compatible with inflammatory disinhibition.…”
Section: Introductionmentioning
confidence: 79%
“…The heterogeneous clinical symptoms parallel broad biological dysfunction in the hypothalamic-pituitary axis (HPA) (2)(3)(4)(5)(6)(7)(8)(9)(10) and autonomic (ANS) (4,(11)(12)(13) and central nervous system (CNS) functions (14)(15)(16)(17). Previous studies have provided evidence for a low level pro-inflammatory state in PTSD (18)(19)(20)(21)(22). The CNS areas involved are central regulators of the HPA axis and the ANS, and this coordinated dysfunction in PTSD is compatible with inflammatory disinhibition.…”
Section: Introductionmentioning
confidence: 79%
“…Three case reports have shown the beneficial effects of topiramate, a GABA agonist and glutamatergic antagonist, in treatment of NES. 30 , 85 , 97 In these case reports, it was shown that adding topiramate treatment to ongoing treatments improved NES symptoms and led to significant weight loss. However, after dose reduction or treatment discontinuation, NES symptoms had returned in these patients.…”
Section: Pharmaceutical Treatment Of Nesmentioning
confidence: 94%
“…Winkelman (2003) observed a reduction in nocturnal awakenings with food intake, improved sleep and weight loss in two patients who failed prior treatments with psychotherapy and pharmacotherapy. 35 Tucker et al (2004) reported the case of a 40-year-old obese woman treated with topiramate for 8 months, who achieved reduction in episodes of nocturnal awakenings accompanied by food intake. 36 Cooper-Kazaz (2012) reported the case of a non-obese female patient under treatment for depression with venlafaxine, who developed NES and weight gain.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…35 Tucker et al (2004) reported the case of a 40-year-old obese woman treated with topiramate for 8 months, who achieved reduction in episodes of nocturnal awakenings accompanied by food intake. 36 Cooper-Kazaz (2012) reported the case of a non-obese female patient under treatment for depression with venlafaxine, who developed NES and weight gain. She received topiramate for 6 weeks, with improvement of night eating symptoms, sleep quality, self-esteem and well-being, and weight loss.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation